Efeito das variações de temperatura na expressão gênica no intestino médio de Aedes aegypti e suas implicações para a interação com Zika virus - Ferreira, Priscila Gonçalves (2022)
The continuous discovery of new pathogens and the emergence of new transmission forms reveal a constant threat to public health. Added to that, climate change can to be an aggravating factor on pathogen transmission. Vector-borne infections represent a major public health challenge and however, we are only just beginning to understand the complexity underlying mosquito–pathogen interactions and how abiotic factors, as temperature affect these interactions. To understand better the temperature effects on vector physiology and its effects on mosquito-pathogen, we compared the transcriptome of mosquito midgut samples from mosquitoes exposed to Zika virus (ZIKV) and non-exposed mosquitoes housed at three different temperatures (20, 28, and 36°C) during 24 and 48 hours of exposure. Initially, the quantification of viral RNA copy number does not show difference between 24 and 48 h post-exposure at 20°C, suggesting that ZIKV replication is limited by cold-induced changes to the mosquito midgut environment. Genes encoding proteins involved in blood digestion, ROS metabolism and mosquito immunity were the ones that showed the greatest change in expression at 20ºC. From these results, we hypothesize that temperature variation affects the blood digestion process, modulating the generation of reactive oxygen species (ROS) in the midgut. We show that temperature variation affects both the expression of genes involved in blood digestion and the rate of digestion. Additionally, due to temperature effects on ROS levels and the expression of antioxidant proteins in the midgut, lower temperatures (20°C) result in a longer state of oxidative stress when compared to other temperatures (28 and 36°C). Finally, alternative splicing events were investigate under different temperatures. Interestingly, among listed genes, we found Trypsin (TRY), Ferritin (FER), Thioredoxin (TRX) and Peptidoglycan recognition protein LC (PGRP-LC), genes previously shown to have their expression modulated by temperature. Our results reveal the physiological processes that are impacted by temperature variation and suggest how the immune response is modulated against Zika virus infection.Keywords: Aedes aegypti. Temperature. Zika virus. Transcriptome. Alternative Splicing.